[OP.3A.06] LONG TERM FOLLOW-UP IN PATIENTS OPERATED ON A PHEOCHROMOCYTOMA OR A PARAGANGLIOMA: COMPILATION OF THE ENS@T DATABASE. (September 2016) - Amar, L.; Deutschbein, T.; Piscaer, I.; Brugger, C.; Canu, L.; Bertherat, J.; Lepoutre, C.; Dekkers, O.; Stell, A.; Gimenez-roqueplo, A.; Fassnacht, M.; Robledo, M.; et al.
Abstract : Objective: Following resection of the primary tumor, patients with pheochromocytoma or paragangliomas (PPGL) are at risk of tumor persistence or tumor recurrence (new PPGL, local recurrence or distant metastasis). However, there are no robust prognostic indices of tumor recurrence in patients with PPGGL cured after surgery to guide clinical practice. The PPGL-ENSAT database was studied retrospectively Figure. No caption available. Design and method: Data from 6 European centers were compiled, including 1153 patients with PPGL. Among them 701 patients met the inclusion criteria: (i) resection of the primary tumor, (ii) no evidence of persistent disease at postoperative assessment, and (iii) documented follow-up of 6 months or more. The ENS@T cohort gave access to individual data and enabled univariate and multivariate analysis of candidate prognostic markers. Results: Among the 701 patients, 54% were women, 80% had a least one pheochromocytoma and 34% had a genetic or syndromic disease. Median age at surgery was 46 years [interquartile range (IQR) 33, 57]. Median follow-up was 54 months [IQR 25, 101]. The risk of new events in the whole population was 10% (95% confidence interval (CI) 8, 14) over the first 5 years of follow-up. Among the new events 45% were metastatic recurrences, 42% were new tumors and 13% were local recurrence. The recurrence were more frequent in patients with paragangliomas versus pheochromocytomas, in patients with tumors size > 150 mm, in patients younger than 20 years at diagnosis of PPGL and in patients with genetic disease (cf table). The incidence of new events did not decline after 5 years of follow-up, but estimates are imprecise after 10 years. Conclusions: At least 10% of the patients will have a recurrence during follow up. All patients should therefore be followed to detect these recurrences.